Exploring the unknown: the language use of German RE-students writing texts about God - Altmeyer, Stefan (British journal of religious education, 2015)
Language does not only play an active part in all processes of comprehension, recognition and learning, it is also essential for specific religious learning processes. Religious experiences and traditions have their own characteristic linguistic forms, and religious education has come to realise the necessity for an appropriate sensibility in religious language. Yet while linguistic features of religion or tradition have been widely discussed and developed, the use of religious language with regard to the learning subjects remains a significant, if not unknown, variable. What do we actually know about the religious language of students? How do we systematically assess their linguistic competence? By presenting selected results regarding the God-talk of German secondary school students, this paper shows how empirical research based on a corpus linguistic approach can provide access to the use of religious language. As such, the paper first aims to initiate a paradigm shift from looking at the linguistic features of content to exploring the language use of learners. Second, it aims to present a research framework that offers possibilities for further comparable and comparative research well beyond the original German speaking context.